TOBACCO LOBBY PUSHING SMOKERS RIGHTS BILL (Tufts Archival Research Center, 2007)
New York Times article on a New Jersey bill protecting smoker's rights in the workplace. Explains that the bill would provide civil rights to smokers and make employment discrimination based on smoking status illegal. Reports that the New Jersey Senate voted to override Governor Florio’s veto.